Errata: "What Is Technical Writing Style Today?" from the Oct.-Nov. 1978 issue - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1979)
Correction Wales and Ashman, "What Is Technical Writing Style Today?" Oct.-Nov. 1978 issue, pp. 13-22.